Hepatic proteomic assessment of oral ingestion of titanium dioxide nano fiber (TDNF) in Sprague Dawley rats. Issue 13 (6th December 2022) - Gato, Worlanyo E.; Wu, Ji; Appiah, Isaac; Smith, Olivia; Rochani, Haresh
Abstract: Titanium dioxide nanofibers (TDNF) have been widely employed in pigments, sunscreens, paints, ointments, toothpaste and photocatalytic splitting of water. However, their potential toxicity has not been thoroughly examined. The goal of the present study is to examine hepatic effects associated with the ingestion of TDNF. TDNF was fabricated via electrospinning method and characterized. Six to seven weeks old male Sprague Dawley rats ingested (oral gavage) a total of 0 ppm, 40, 60 ppm TDNF for two weeks. After sacrifice, the liver was assessed for cellular effects using proteomic approach. The fibers diameter ranged from 0.18 − 0.29 μm, forming clusters and majority of the fibers were in the rutile phase. Proteomics assessment revealed more that more than 400 hundred proteins in the liver may be affected. These proteins are involved in such processes as catalysis of fatty acids by CoA, homocysteine metabolism, beta oxidation and the condensation of carbamoyl phosphate in the urea cycle among others. Further analysis of the protein associations showed that 325 biological processes, 140 molecular functions and 70 cellular components appear to be affected from the ingestion of TNDF. Quantitative analysis of specific mRNA transcripts indicated CMBL, GSTM1 and SDS were differentially expressed.